2010
DOI: 10.1103/physreve.82.051906
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and force-generated cooperativity in a theory of DNA-bending proteins

Abstract: We study a statistical-mechanical model of the binding of DNA-bending proteins to the double helix including applied tension and binding cooperativity effects. Intrinsic cooperativity of binding sharpens force-extension curves and causes enhancement of fluctuation of extension and protein occupation. This model also allows us to estimate the intrinsic cooperativity in experiments by measuring the peak value of the slope of extension versus chemical-potential curves. This analysis suggests the presence of force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…(47) gives the two correct limits far from the transition Eqs. (45,46). In the fitting procedure, the parameter κ BS plays a similar role as the parameter J (see Eq.…”
Section: A Overstretching Transition For Poly(dg-dc) and λ-Dna Arounmentioning
confidence: 99%
See 3 more Smart Citations
“…(47) gives the two correct limits far from the transition Eqs. (45,46). In the fitting procedure, the parameter κ BS plays a similar role as the parameter J (see Eq.…”
Section: A Overstretching Transition For Poly(dg-dc) and λ-Dna Arounmentioning
confidence: 99%
“…The partition function is Z = (4π) N ±, (2 + 1)λ N ,± in case of periodic boundary conditions and by Z = (4π) N ,± V |0, ± 2 λ N ,± in case of free ends (where |V is the adequate free-end vector) [32]. Of course, boundary conditions are irrelevant at large N [45], and we have checked that finite size effects are negligible for the DNAs studied in the experiments considered in the following.…”
Section: Analytical Model For B To S-dna Transitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a later paper, Zhang and Marko considered a type of cooperativity that could potentially describe protein¯laments; however, their study focused on force-extension curves. 18 Speci¯cally, they reported that even moderate amounts of adjacent-site cooperative energy could strongly a®ect the force-extension pro¯les. Olson and co-workers took the modeling of HU-DNA complexes beyond the traditional statistical mechanics approach by considering realistic three-dimensional (3D) structural and mechanical features.…”
Section: Introductionmentioning
confidence: 99%